Surgical techniques to preserve continence after robot-assisted radical prostatectomy - Katsimperis, Stamatios; Juliebø-Jones, Patrick; Ta, Anthony; Tandogdu, Zafer; Al-Bermani, Osama; Bellos, Themistoklis; Esperto, Francesco; Tonyali, Senol; Mitsogiannis, Iraklis; Skolarikos, Andreas; Varkarakis, Ioannis; Somani, Bhaskar K.; et al. (Frontiers in Surgery, 2023)
Radical prostatectomy significantly impacts the inherent anatomy of the male pelvis and the functional mechanisms of urinary continence. Incontinence has a considerable negative influence on the quality of life of patients, as well as their social and psychological wellbeing. Numerous surgical techniques have been demonstrated to support the preservation of continence during robot-assisted radical prostatectomy (RARP). In this in-depth analysis, we give a general summary of the surgical techniques used in RARP and their impact on incontinence rates.